IMPACT OF CAREER CHOICE ON LEARNING OF MEDICAL STUDENTS - Rehman, Rehana; Hoor, Talea; Habib, Sana; Kamran, Ambreen (Journal of Postgraduate Medical Institute, 2014)
Objective: To observe the effect of selection of profession on learning ofmedical students. Methodology: It was a cross sectional questionnaire based study conductedfrom February 2009 till 2012 on first year medical students of Bahria University Medical & Dental College. Students were stratified into two groups on thebasis of selection of profession on their own (Group A) and by compulsion as(Group B). The responses in terms of active learning were acquired by participationin group discussions, work based learning, interaction with teachers,and peers. The frequencies of responses were analyzed and both groups comparedby chi square test. Results: Group A (Opted) comprised of 263 (71%) students as compare to 105(29 %) students in Group B (p<0.001). Group A had 248 (94%) girls whereas65 (62%) boys were there in group B. Participation in discussions 231 (88%) ofGroup A was significant as compared to 73 (70%) in group B; p=0.01. Criticalreasoning in Group A students; 229 (87%), was more in comparison to 73(70%) in Group B (p=0.04). Interaction with teachers and peers was in GroupA was identical 229(87%) vs. 65(62%) and 81(77%) in Group B respectively;p=0.0001, 0.014. Group A students were confident, explored personal attitudes,worked in group and improved by feedbacks. Conclusion: Majority of students predominantly the females selected medicalprofession on choice. This selection was reflected on learning of students andthey were found to be active learners.